Advantages of application of mycorrhizated plants in environmentfriendly agriculture and forestations - Bratek, Zoltán (Acta Biologica Szegediensis, 2002)
Ectomycorrhizal inoculation procedures have been developed to improve forestation practice in areas with unfavourable habitat properties. The inoculation of cultivated crops with specially developed inocula of arbuscular-mycorrhizal fungi succeeded in reaching a substantial harvest surplus of plant material, and makes environment-friendly, fertilizer-free farming practices around shallow lakes possible.